The digital promise - pedagogy transformation using digital learning in tertiary education - Mangair Karasi Manickam, *; Premanand Krishnamurthy, * (Sunway College Kuala Lumpur, 2015)
This paper describes pedagogical transformation using digital learning, which promotes enhanced teaching and learning in tertiary education and evaluates the end-user computing (EUC) satisfaction of digital change using various tools like forum, online quizzes, distribution of lecture notes and file sharing. The research will use a quantitative method to analyse the effectiveness of digital learning among tertiary learners. The learners can be an important source of information in evaluating the quality of digital learning interface and its effectiveness. The research survey questionnaire will be distributed through a specific Learning Management System (LMS) and the effectiveness will be analysed upon the completion of data gathering. This study is important to analyse student’s expectation and to enhance digital learning utilisation.